Psychological Influence of Advertising Billboards on City Sight - Sharifi Nowghabi, Azadeh; Talebzadeh, Adeleh (Salehan Institute of Higher Education, 2019)
The most important contributions of metropolitan cities to modernity is its noise pollution and visual, and structural disturbances in urban life. Due to the fact that these cities have entered into a new world that has not experienced any of its principles before it has tested the urban structure and has a proper connection between the needs of the inhabitants and even the dominant tradition and culture. City billboards and advertisements have doubled the visual disturbances in this new sovereignty of urbanization; this kind of visual pollution causes mental confusion and reduces the intellectual concentration of individuals, and its effects and consequences is progressing through time. The images in the city's atmosphere, including buildings, streets, traffic signs and commercial and exterior signs of buildings and stores, various billboards and urban furniture, and other elements that are exposed to the public, have different colors which have different psychological effects on viewers. Color as one of the most important visual elements can have an active and influential effect on the general public's perspective of the city and its psychological effects on its citizens. The question is whether a suitable solution could be made to regulate the types of commercial billboards and, thus, provide psychological comfort and safety for citizens. This study has used library resources, internet data and survey method and analysed them after observing and investigating the collected data and the analysis of colors in advertising billboards and their layout along with their psychological effects, especially in the intersection of the crowded streets of Mashhad. In addition to searching for major problems in urban advertising in terms of environmental qualities, the researchers have tried to provide appropriate solutions to the challenge through visual comfort components and their evaluation. The results of this research show that the promotion of the level of visual components, including color in advertising, and in particular at the intersection of streets and congestion of traffic signs and warning signs, has a profound effect on urban landscape. Accordingly, encouraging the use of appropriate advertising equipment and providing appropriate solutions for organizing and institutionalizing urban advertising, will enhance its quality and create order and beauty in the environment, and thus provide visual comfort to citizens.